POLA PERGERAKAN WANITA PENJAJA SEKS (WPS) DI KOTA PADANG - Jilham Jilham; Paus Iskarni; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2017)
The study aims to: 1) Mapping the movement patterns of sex workers (FSW) in Padang. 2) Knowing the factors that affect a person become sex workers (FSW) in Padang.This qualitative research is descriptive and tend to use qualitative analysis. The sample consists of three elements, namely where (place), actors (actor), and activity (activity). The sampling technique is snowball sampling as many as twenty-five (25) sex workers. Data Analysis Techniques Analysis Pattern is Movement and Cross Tabulation Analysis (crosstabs).The results of this research are: 1) Based on the analysis of movement patterns sourced from Alan Leu and Bob McKercher (2006) movement patterns of sex workers (FSW) in Padang classified patterns Multiple Pattern types Chaining Loop as much as 48% and Base Site as much as 28% , 2) Factors that affect a person become sex workers in the city of Padang is more dominant factors, namely the weak economy as much as 60%.